Psychological and pedagogical strategies for the development of the subjectivity of a modern adolescent. - Ishonkulova Norbie Islamovna; Iskhakova Gulbokhor Ismoilovna (International Journal on Orange Technologies, 2021)
In domestic psychology, a rich experience was accumulated on the study of the problem of a person as a subject of activity and vital activity. Consideration of a person as a subject is a fundamental problem of human psychology. The subject in the philosophical and psychological literature is defined as the bearer of object-oriented practical activity and cognition, a source of activity aimed at the object. In this regard, the tasks of forming adolescents' self-awareness, critical self-esteem and a positive attitude towards the possibilities of their development, the ability to independently determine the goals of their lives, as well as the ability to self-projection into the future acquire particular relevance.